Pontos de vista de fisioterapeutas envolvidos na produção e disseminação de conhecimento sobre a Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF) no Brasil: um estudo Q - Rafaela Cristina de Souza Arrais Albuquerque (2023)
The International Classification of Functioning, Disability and Health (ICF) proposes a paradigm shift from the biomedical to the biopsychosocial model. The ICF provides a conceptual framework and a classification system that offers a common language for understanding and examining functionality and disability within the context of research, education, and clinical practice in physical therapy. However, there may be considerable variation in the interpretation of the components and concepts of the ICF and their interrelationships, influencing clinical thinking, professional decision-making, and the dissemination of knowledge about functionality. Therefore, this study aimed to characterize the circulating discourses regarding the ICF among expert physical therapists involved in the study, teaching, and research of the topic in Brazil, using the Q methodology. The methodology consists of 6 steps: creating a Q-concourse (a broad set of statements about the ICF), developing the Q-set (a subset of representative statements), selecting the participant set (P-set), participants ranking the Q-set statements by agreement (Q-sort), factor analysis, interpretation, and naming of collective viewpoints through qualitative synthesis. Through an observational cross-sectional study of viewpoints on the ICF using the Q methodology, a Q-concourse was created with over 500 statements extracted from key references on the topic, resulting in a Q-set with 59 statements. The P-set was composed of 48 participants from different regions of Brazil working in different physiotherapy specialties. The average years of education in physiotherapy were 19.1+6.6 years, with 52% having graduated from public universities in Brazil, and 77% holding a doctoral or postdoctoral degree. The average years of teaching experience were 13.62+6.93 years, and the average years of working with the ICF were 16.04+4.93 years. From the factor analysis using Ken-Q Analysis software, two factors emerged (representing distinct viewpoints) with 32 statements showing significant average rank differences (p<0.05) between them, and 27 statements with no significant rank differences. The two factors were interpreted as viewpoints named pragmatic and conceptual, both complementary in terms of how they value the ICF. Both viewpoints endorsed a biopsychosocial perspective and showed no clear stance about criticisms of the ICF. The viewpoints prompt reflections that can have a significant impact on the national debate about functionality.